First report of Vandellia sp. parasiting the Raspy river stingray Potamotrygon scobina in the Amazon basin - Paulo Arthur Abreu Trindade; Felipe Antônio Silva Jr; Marcos Sidney Brito Oliveira; Carson Allen Jeffres; Marcelo Ândrade; Tommaso Giarrizzo (Revista Brasileira de Parasitologia Veterinária)
Abstract This study reports the first record of candiru, Vandellia sp. parasitizing the freshwater stingray Potamotrygon scobina in the Amazon basin, Brazil. In April 2018, a specimen of Potamotrygon scobina was collected by bottom long-term using fish as bait during the monitoring program in the Xingu River. During a routine inspection, a Vandellia sp. was observed in the branchial slit of the Potamotrygon scobina specimen. The trichomycterid was collected and preserved in 10% formaldehyde followed by preservation in 70% ethanol. This study is the first to record this parasite associated on a stingray in Brazil.